Adherence to the Mediterranean diet and risk of bladder cancer in the EPIC cohort study - Buckland, G; Ros, M; Roswall, N; Bueno-De-Mesquita, H; Travier, N; Tjonneland, A; Kiemeney, L; Sacerdote, C; Tumino, R; Ljungberg, B; Gram, I; Weiderpass, E; et al. (Wiley-Liss Inc., 2014)
There is growing evidence of the protective role of the Mediterranean diet (MD) on cancer. However, to date no epidemiological study has investigated the influence of the MD on bladder cancer. We evaluated the association between adherence to the MD and risk of urothelial cell bladder cancer (UCC), according to tumor aggressiveness, in the European Prospective Investigation into Cancer and Nutrition (EPIC). The analysis included 477,312 participants, recruited from ten European countries between 1991 and 2000. Information from validated dietary questionnaires was used to develop a relative Mediterranean diet score (rMED), including nine dietary components. Cox regression models were used to assess the effect of the rMED on UCC risk, while adjusting for dietary energy and tobacco smoking of any kind. Stratified analyses were performed by sex, BMI, smoking status, European region and age at diagnosis. During an average follow-up of 11 years, 1,425 participants (70.9% male) were diagnosed with a first primary UCC. There was a negative but non-significant association between a high versus low rMED score and risk of UCC overall (HR: 0.84 [95% CI 0.69, 1.03]) and risk of aggressive (HR: 0.88 [95% CI 0.61, 1.28]) and non-aggressive tumors (HR: 0.78 [95% CI 0.54, 1.14]). Although there was no effect modification in the stratified analyses, there was a significant 34% (p = 0.043) decreased risk of UCC in current smokers with a high rMED score. In EPIC, the MD was not significantly associated with risk of UCC, although we cannot exclude that a MD may reduce risk in current smokers. © 2013 UICC.